Cancer Epigenetics: Biomolecular Therapeutics for Human Cancer. Edited by Antonio Giordano and Marcella Macaluso. Issue 6 (22nd April 2013) - Blagg, Julian
<x xml:space="preserve">Abstract</x> Wiley–Blackwell, Hoboken 2011. 436 pp., hardcover, $149.95.—ISBN 978‐0‐471‐71096‐7<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>